Photonic, spectroscopic properties and electronic structure of PTCDI-C8 organic nanostructure - Gündüz, Bayram; Kurban M. (Elsevier B.V., 2018)
The changes in the structural, electronic, vibrational and photonic properties of N,N?-Dioctyl-3,4,9,10-perylenedicarboximide (PTCDI-C8) one-dimensional nanostucture have been investigated using experimental and theoretical techniques. The semi-empirical relations have been proposed for the calculation of the refractive index nfrom its measured and calculated energy gap Eg data. FT-IR and FT-Raman spectra characteristics and structural, spectroscopic and electronic properties such as HOMO-LUMO energies, harmonic frequencies, Mullkien atomic charges, dipole moments, radial distribution functions (RDFs) and coordination number of binary interactions were recorded with the aid of density functional theory (DFT) based on optimized structure for gas phase and different solvent environments. Moreover, ultraviolet-visible (UV–vis) spectral analysis and energy gaps has been carried out using experimental techniques and time-dependent (TD) DFT calculations. The results herein obtained reveal that PTCDI-C8 material is suitable for sensitivity applications due to its appropriate optoelectronic paramaters. © 2018 Elsevier B.V.
Keywords: Density-functional theory; Electronic properties; Optical techniques; Photonic properties; Structure analysis